UNC93B1 mediates differential trafficking of endosomal TLRs - Lee, Bettina L; Moon, Joanne E; Shu, Jeffrey H; Yuan, Lin; Newman, Zachary R; Schekman, Randy; Barton, Gregory M (eLife, 2013)
UNC93B1, a multipass transmembrane protein required for TLR3, TLR7, TLR9, TLR11, TLR12, and TLR13 function, controls trafficking of TLRs from the endoplasmic reticulum (ER) to endolysosomes. The mechanisms by which UNC93B1 mediates these regulatory effects remain unclear. Here, we demonstrate that UNC93B1 enters the secretory pathway and directly controls the packaging of TLRs into COPII vesicles that bud from the ER. Unlike other COPII loading factors, UNC93B1 remains associated with the TLRs through post-Golgi sorting steps. Unexpectedly, these steps are different among endosomal TLRs. TLR9 requires UNC93B1-mediated recruitment of adaptor protein complex 2 (AP-2) for delivery to endolysosomes while TLR7, TLR11, TLR12, and TLR13 utilize alternative trafficking pathways. Thus, our study describes a mechanism for differential sorting of endosomal TLRs by UNC93B1, which may explain the distinct roles played by these receptors in certain autoimmune diseases. Toll-like receptors (TLRs) are proteins that are responsible for recognizing specific molecules associated with invading pathogens, known as pathogen-associated molecular patterns. Upon detecting these signals, TLRs activate the body's immune response, which fights the infection. A subset of TLRs recognizes nucleic acids, including DNA and RNA, enabling the immune system to respond to foreign material from a diverse range of bacteria and viruses. However, some of the body's own DNA and RNA is also found outside cells (e.g., in the bloodstream) and TLRs must be able to discriminate between these nucleic acids and those belonging to pathogens, because failure to tell the difference between the two could result in autoimmune disease. To reduce this risk, TLRs are sequestered inside the cell within membrane-bound compartments known as endosomes. UNC93B1 is a transmembrane protein that is known to control the movement of TLRs from the endoplasmic reticulum—where TLRs are assembled—to endosomes. However, the exact mechanisms by which this protein controls TLR trafficking were unclear. Now Lee et al. reveal that it directly controls the packaging of at least six TLRs at the endoplasmic reticulum: it helps to load these TLRs into vesicles, which are in turn processed by the Golgi apparatus—the organelle wherein proteins are sorted and packaged en route to their final destinations. Surprisingly, UNC93B1 remains associated with the TLRs even after Golgi processing. Lee et al. also reveal that specific endosomal TLRs are subject to distinct post-Golgi trafficking mechanisms. In order for TLR9 to be delivered to the endosome, UNC93B1 must recruit an adaptor protein called AP-2, whereas other TLRs appear to require different actions by UNC93B1. By defining the mechanisms that underlie the differential trafficking of endosomal TLRs, Lee et al. suggest that we may learn how to manipulate distinct aspects of TLR activation, and also gain insights into the causes of certain autoimmune diseases.